A case of primary nonleukemic myeloid sarcoma of the spleen, successfully treated by surgery and hematopoietic stem cell transplantation - Asuka Ono; Yuki Kitano; Katsunori Imai; Takashi Matsumoto; Shinya Endo; Kenji Tokunaga; Hiromitsu Hayashi; Yo-Ichi Yamashita; Masao Matsuoka; Hideo Baba (Surgical Case Reports)
Abstract Background Myeloid sarcoma (MS) is a rare disease, mostly found in conjunction with acute myelogenous leukemia or other diseases, and primary nonleukemic MS of the spleen is particularly rare. Case presentation We report a 57-year-old male who presented with a spleen mass that was found incidentally, and was enlarged. As a result of various examinations, he was diagnosed with primary MS of the spleen with suspected involvement of the transverse colon, left kidney, pancreatic tail, and left diaphragm. He underwent a total splenectomy, partial pancreatectomy, partial colectomy, left nephrectomy, and left diaphragm partial resection. Histological examination revealed splenic primary MS. Bone marrow biopsy and immunophenotypic flow cytometry revealed no evidence of myeloid leukemia. He underwent umbilical cord blood transplantation, and he is currently living without a sign of recurrence at 10 months after surgery. Conclusions We experienced a very rare case of primary spleen MS that was discovered without a hematologic malignancy. Two cases of surgically resected primary splenic MS have been reported, including the present case.